Life-history traits drive spatial genetic structuring in Dinaric cave spiders - Pavlek, Martina; Gauthier, Jérémy; Tonzo, Vanina; Bilat, Julia; Arnedo, Miquel A.; Alvarez, Nadir (Frontiers in Ecology and Evolution, 2022)
The subterranean cave exerts strong selection pressures on the organisms that thrive in it. In response, obligate cave-dwellers have developed a series of morphological, physiological and behavioural adaptations, such as eye reduction, appendage elongation, low metabolic rates or intermittent activity patterns, collectively referred to as troglomorphism. Traditionally, studies on cave organisms have been hampered by the difficulty of sampling (i.e., small population sizes, temporal heterogeneity in specimen occurrence, challenges imposed by the difficult-to-access nature of caves). Here, we circumvent this limitation by implementing a museomics approach. Specifically, we aim at comparing the genetic population structures of five cave spider species demonstrating contrasting life histories and levels of troglomorphism across different caves in the northern Dinarides (Croatia, Europe). We applied a genome-wide hybridization-capture approach (i.e., HyRAD) to capture DNA from 177 historical samples. By comparing the population genetic structures among five species and by studying isolation by distance, we identified deeper population structuring and more pronounced patterns of isolation by distance in the highly troglomorphic Parastalita stygia and Stalita pretneri ground dwellers, while the three web-building Troglohyphantes species, two of which can occasionally be found in surface habitats, showed less structured populations compatible with higher dispersal ability. The spatial distribution of genetic groups revealed common phylogeographic breaks among lineages across the studied species, which hint at the importance of environmental features in driving dispersal potential and shaping underground diversity.